Resist : a story of D-Day - Gratz, Alan, 1972- (New York : Scholastic Press, 2025)
"When French-Algerian Samira's mother is arrested by the Nazis, Samira must go on a journey through Nazi-occupied France to save her before it is too late...on the same day as D-Day"--
Ages 9-12.
Grades 4-6.
Keywords: World War, 1939-1945 -- Campaigns -- France -- Normandy -- Fiction; Government, Resistance to -- Fiction; France -- History -- 20th century -- Fiction; Historical fiction; War fiction; Novels